Impact of Credit Risks on Profitability of the Licensed Commercial Banks in Sri Lanka - Mithila, G.; Kengatharan, L. (Open University of Sri Lanka, 2023)
Effective credit risk management and application of various credit management techniques are crucial for the success of the commercial banks globally. The focus of this paper is to assess the impact of credit risk management on the financial performance of licensed commercial banks in Sri Lanka. The research paradigm of the study is positivist. For this study, six systematically important banks which hold approximately 53% of the market share, are selected by using a stratified sampling technique for the periods of 2017 to 2021.The Independent variable of the study is return on equity (ROE) while non-performing loan ratio (NPL), capital adequacy ratio (CAR), total loan to assets ratio (LTA) and total loan to deposits ratio (LTD) are employed to measure the credit risks of the commercial banks. In order to ensure the selected data of the banks are normally distributed, with no multicollinearity in explanatory variables, no heteroscedasticity in the variables, the Jarque Bera test, variance, inflation factor test and White test are conducted respectively. Further, Pooled OLS, Fixed effect and Random effect models are applied to test the hypotheses, and by using Breusch and Pagan LM test, Hausman test the most suitable model for this analysis is chosen. Based on the diagnostic tests, it is confirmed that data taken for the analysis are normally distributed, no multicollinearity among explanatory variables and no heteroscedasticity errors. From fixed, random and Pooled OLS tests, the study revealed that Pooled OLS is most suitable to test the impact of credit risk on profitability. Coefficient of determination (Adjusted R2) is approximately 74%. This confirms that variability in profitability is explained by dependent variables which are taken for this study namely NPL, LTA, LTD and CAR. Further, there is a negative significant impact from NPL and LTD on the profitability of licensed commercial banks while LTA has a positive significant impact. However, CAR does not have significant impact on the profitability. Therefore, the study ensures a profound relationship between credit risk and performance of banks and recommends banks to assess and implement credit risk measuring tools to improve the performances. This includes implementing effective credit risk management policies and procedures, monitoring loan quality, and diversifying their loan portfolios.